2016
DOI: 10.1080/14992027.2016.1219073
|View full text |Cite
|
Sign up to set email alerts
|

Lexical tone recognition in noise in normal-hearing children and prelingually deafened children with cochlear implants

Abstract: Objective The purpose of the present study was to investigate Mandarin tone recognition in background noise in children with cochlear implants (CIs), and to examine the potential factors contributing to their performance. Design Tone recognition was tested using a two-alternative forced-choice paradigm in various signal-to-noise ratio (SNR) conditions (i.e., quiet, +12, +6, 0, and −6 dB). Linear correlation analysis was performed to examine possible relationships between the tone-recognition performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 43 publications
5
33
0
Order By: Relevance
“…These reports have shown that CI provides a fairly high level of speech perception in the majority of users, especially in quiet conditions. However, other reports have indicated that CI recipients exhibit considerable deficits in tone perception of native tonal language speakers, especially among prelingually deafened tonal language children …”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…These reports have shown that CI provides a fairly high level of speech perception in the majority of users, especially in quiet conditions. However, other reports have indicated that CI recipients exhibit considerable deficits in tone perception of native tonal language speakers, especially among prelingually deafened tonal language children …”
Section: Introductionmentioning
confidence: 93%
“…However, other reports have indicated that CI recipients exhibit considerable deficits in tone perception of native tonal language speakers, especially among prelingually deafened tonal language children. [4][5][6][7][8][9][10][11][12][13] Sound-processing strategies are the core of CI technology, which transform speech into stimuli for the electrodes. Most sound-processing strategies have been designed based on the languages of Europe and the United States, which differ from tonal languages, that is, Sino-Tibetan, including Mandarin and Cantonese.…”
Section: Introductionmentioning
confidence: 99%
“…English. Tone information is particularly important for tonal language and speech 136 recognition in noise (Mao & Xu, 2016). Thus, poor pitch information conveyed by 137…”
Section: Factors Affecting Speech Perception 116mentioning
confidence: 99%
“…Seven 210 studies were cross-sectional (Y. Chen, Wong, Chen, & Xi, 2014;Han et al, 2009;211 A. Li, Wang, Li, Zhang, & Liu, 2014;Mao & Xu, 2016;Tao et al, 2015;Xu et al, 212 2011;Zhou, Huang, Chen, & Xu, 2013) and one is a review (Tan, Dowell, & Vogel, 213 2016). None of the tone perception tests used in these studies had been standardized, 214 which was the major source of bias.…”
Section: The Trajectories In Speech Perception Development In Mandarimentioning
confidence: 99%
See 1 more Smart Citation